Soybean - The Basis of Yield, Biomass and Productivity 2017
DOI: 10.5772/67157
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Yield Responses to Micronutrient Fertilizers

Abstract: The availability of commercial products containing micronutrients for the management of crops has increased in recent years, but there are experimental results showing great variability in response to their application. A literature review was made in 28 scientific articles about the answers in the soybean yield in Brazilian agriculture due to the application of fertilizer containing micronutrients. Then, the aim of this chapter is to approach the efficiency of sources, doses, application methods, time, and yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Before applying a Mn fertilizer, it is important to determine whether sample soils or plants need this element. As suggested by Lacerda et al (2017), the most important aspect when applying micronutrients in the soil, topdressing or seed furrow, foliar or seed treatment, is the application time and dosage of micronutrients to provide the nutrients in adequate amounts the plant requires. In many areas of the world Mn as foliar application is recommended in calcareous soils.…”
Section: D) Seed Treatmentmentioning
confidence: 99%
“…Before applying a Mn fertilizer, it is important to determine whether sample soils or plants need this element. As suggested by Lacerda et al (2017), the most important aspect when applying micronutrients in the soil, topdressing or seed furrow, foliar or seed treatment, is the application time and dosage of micronutrients to provide the nutrients in adequate amounts the plant requires. In many areas of the world Mn as foliar application is recommended in calcareous soils.…”
Section: D) Seed Treatmentmentioning
confidence: 99%
“…Sutradhar et al (2017) and Calonego et al (2010) also reported increased leaf B content of 24% and 39%, respectively, and did not observe any increase in soybean yield. Lacerda et al (2017) attributed the unresponsiveness of the soybean crop to B fertilization reported by Calonego et al (2010) to high soil B availability; contents were 0.43 mg dm -3 at the study site. Other authors have also associated soybean unresponsiveness with B foliar application to its low efficiency (Seidel et al, 2015;Bruns, 2017;Nakao et al, 2018;Santos et al, 2019;Ratke et al, 2020).…”
Section: Resultsmentioning
confidence: 78%
“…Manganese in soybean crops is applied through foliar application in the form of manganese sulfate. Manganese availability to soybean crops depends particularly upon tillage, organic matter content, and tillage [48]. e problem of manganese deficiency is more common in areas having flood and water fluctuations.…”
Section: Manganesementioning
confidence: 99%
“…According to [23], 55 g of boron is required to produce one ton of soybean seed yield. Boron uptake by the plants is in the form of boric acid (H 3 BO 3 ), which is available in soil solution in a soluble form [48]. e other important source of boron is soil organic matter, which becomes available through microbial activity.…”
Section: Boronmentioning
confidence: 99%